PENGARUH TEKNOLOGI INFORMASI DAN SOCIAL MEDIA MARKETING TERHADAP MINAT BELI (Studi Kasus CV. SOREN Di Salatiga) - Prasetyo, Dwi; Rahayu, Listyowati Puji; Safitri, Unna Ria (EKOBIS, 2025)
This study aims to determine the influence of Information Technology and Social Media Marketing on Purchase Intention (Case Study of CV.SOREN in Salatiga) partially and simultaneously. Sampling method with purposive sampling technique. The primary research data was obtained by distributing questionnaires to 100 respondents containing statements about Information Technology, Social Media Marketing and Purchase Intentions. Data analysis tool with validity and reliability tests. Classical assumption test in the form of Normality test, Autocorrelation test, Heteroscedasticity test, Multicollinearity test. using multiple linear regression analysis, and testing the hypothesis using the t test, F test, and the coefficient of determination. Data processing uses the SPSS 2023 program. With the results of the research, (1) Information Technology has no effect on Purchase Interest, the value of t count < t table, namely the value of 1,833 < 1,984. (2) Social Media Marketing has a significant effect on Purchase Intention t count > t table with a value of 12.864 > 1,984, (3) Information Technology Social Media Marketing has a significant effect on Purchase Intention that the value of F count > F table is 265,813 > 3.09 then the significance value is < 0.05 equal to 0.000 < 0.05.